IRF1 Maintains Optimal Constitutive Expression of Antiviral Genes and Regulates the Early Antiviral Response - Panda, Debasis; Gjinaj, Erisa; Bachu, Mahesh; Squire, Erica; Novatt, Hilary; Ozato, Keiko; Rabin, Ronald L. (Frontiers in Immunology, 2019)
Viral defense at mucosal sites depends on interferons (IFN) and IFN stimulated genes (ISGs), either of which may be constitutively expressed to maintain an “antiviral state” (AVS). However, the mechanisms that govern the AVS are poorly defined. Using a BEAS-2B respiratory epithelial cell line deficient in IRF1, we demonstrate higher susceptibility to infection with vesicular stomatitis virus (VSV) and influenza virus. IRF1-mediated restriction of VSV is IFN-independent, as blockade of types I and III IFNs and JAK-STAT signaling before infection did not affect VSV infection of either parent or IRF1 KO cells. Transcriptome analysis revealed that IRF1 regulates constitutive expression of ~300 genes, including antiviral ISGs: OAS2, BST2, and RNASEL and knockdown of any of these IRF1-dependent genes increased VSV infection. Additionally, IRF1 enhances rapid expression of IFNβ and IFNλ after stimulation with poly I:C and also regulates ISG expression. Mechanistically, IRF1 enhances recruitment of BRD4 to promotor-enhancer regions of ISGs for rapid expression and maintains levels of histone H3K4me1 for optimal constitutive expression. Finally, IRF1 also regulates constitutive expression of TLR2 and TLR3 and promotes signaling through these pattern recognition receptors (PRR). These data reveal multiple roles for IRF1 toward effective anti-viral responses by maintaining IFN-independent constitutive expression of anti-viral ISGs and supporting early IFN-dependent responses to PRR stimulation.